USING THE TECHNOLOGY OF ‘CYBER-HUNTING’ FOR THE DEVELOPMENT OF PROFESSIONAL COMPETENCE OF TEACHERS OF VOCATIONAL COLLEGES (Innovative professional education, 2025)
The article justifies the relevance of the application and characterizes the essence of cyber-hunting as a type of internet project and a manifestation of gamification in the educational process. It explores the potential for implementing this technology in the professional development of instructors in pre-higher education colleges
Keywords: cyber-hunting, teaching technology, professional development, professional competence, pedagogical staff of pre-higher education colleges